Coarctation of Aorta as Shown in CT Aortogram (Journal of Medicine, 2014)
Coarctation of the aorta is a congenital heart disease where there is constriction of Aorta. Coarctation accounts for 15-20 % of congenital cardiac defects and is more common in males than in females. It occurs in 1 of 10,000 live births. Coarctation of the aorta is a condition for which surgical outcomes are good and children will lead normal and healthy lives without restriction of their activity. They will typically catch up in growth and have normal development following the recovery period of the surgery. Coarctation of the aorta is typically treated by surgery to remove the narrowed segment of the aorta. Typically the surgery is best done when the child is between 18 and 24 months of age. Sometimes coarctation can be corrected by a balloon angioplasty procedure done during cardiac catheterization. A plastic tube will be inserted in the narrowed segment and a balloon in the tube will be inflated to stretch the narrowed segment. Sometimes a mess tube is then inserted (called a stent) to hold the vessel open. Some infants will be very sick, requiring care in the intensive care unit (ICU) prior to the procedure and could possibly even need emergency repair of the coarctation. Others, exhibiting few symptoms, will have the repair scheduled on a less urgent basis. A small device, called a stent, may also be placed in the narrowed area after the balloon dilation to keep the aorta open. Overnight observation in the hospital is generally required.DOI: http://dx.doi.org/10.3329/jom.v15i1.19872 J Medicine 2014; 15: 51-54